The Effect of a Differentiated Learning Approach on the Interest in Learning IPAS among Fifth-Grade Students at SD Inpres 12/79 Lonrae - Arnita; Muliadi; Asriadi (PT. Lontara Digitech Indonesia, 2025)
This study is a quantitative study with a correlational research design, which aims to describe the relationship between the differentiated learning approach and the interest in learning IPAS among fifth-grade students at SD Inpres 12/79 Lonrae, Tanete Riattang Timur District, Bone Regency. The population consisted of 29 fifth-grade students, selected using a saturated sampling technique. Data were collected using a questionnaire. The data analysis techniques employed were descriptive statistical analysis and inferential statistical analysis. Based on the results of the descriptive statistical analysis, the mean Pretest score was 51.9, which was categorized as poor, while the mean Posttest score was 81.03, which was categorized as good. The conclusion of this study indicates that there is an effect of implementing the differentiated learning approach on students’ interest in learning IPAS, as reflected in the difference between the mean Pretest and Posttest scores of students’ learning interest.